Kardiochirurgia wad wrodzonych The Ross procedure in a 4-year-old patient with aortic valve malformation and endocarditis after cerebral bleeding - Bartkowski, Rafał; Wojtalik, Michał; Sharma, Girish; Henschke, Jacek; Piaszczyński, Maciej; Westerski, Przemysław; Wodziński, Andrzej; Mrówczyński, Wojciech; Neirotti, Roberto (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2005)
Background: There are two methods of operation in patients with aortic valve malformation: the Ross procedure, and aortic valve replacement (for instance: artificial valve). The Ross procedure is probably better in patients with endocarditis (to avoid reinfection of the artificial valve). Aim: Presentation of a 4-year-old patient after the Ross procedure and evaluation of this method. Material and methods: We present a patient with bicuspid aortic valve after endocarditis and cerebral bleeding. The Ross procedure with bovine Contregra conduit were performed. Results: The patient was extubated on a first day after surgery. In echocardiograhic examination: neoAV 1.6 cm; V max. 0.86, V min. 0.57; PG max. 3.0 mmHg; PG min. 1.6 mmHg; VTI: 0.112; residual AI. NeoPV – xenograft 1.43 cm; MFV=1.3 m/s; V min. 0.89 m/s; PG max. 6.76; PG min. 3.65 mmHg. LV 3.0/2.16 cm; EF=58%. Conclusions: The Ross procedure in a child after endocarditis and cerebral bleeding is probably the best operation in a such situation.